Upgrading the maritime legal and administrative regimes of member states in support of the implementation of a system of Port-State-Control (PSC) in the Caribbean - UNDP (UNDP [S.l.], 1996)
Seeks to support the development of the CARICOM maritime sector by enhancing the Region's ability to effectively regulate its maritime activities, conserve its marine environment and cooperate with other states of the Caribbean to implement a system of Port State Control.